If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -2) = 124 Reorder the terms: x(-2 + x) = 124 (-2 * x + x * x) = 124 (-2x + x2) = 124 Solving -2x + x2 = 124 Solving for variable 'x'. Reorder the terms: -124 + -2x + x2 = 124 + -124 Combine like terms: 124 + -124 = 0 -124 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '124' to each side of the equation. -124 + -2x + 124 + x2 = 0 + 124 Reorder the terms: -124 + 124 + -2x + x2 = 0 + 124 Combine like terms: -124 + 124 = 0 0 + -2x + x2 = 0 + 124 -2x + x2 = 0 + 124 Combine like terms: 0 + 124 = 124 -2x + x2 = 124 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 124 + 1 Reorder the terms: 1 + -2x + x2 = 124 + 1 Combine like terms: 124 + 1 = 125 1 + -2x + x2 = 125 Factor a perfect square on the left side: (x + -1)(x + -1) = 125 Calculate the square root of the right side: 11.180339887 Break this problem into two subproblems by setting (x + -1) equal to 11.180339887 and -11.180339887.Subproblem 1
x + -1 = 11.180339887 Simplifying x + -1 = 11.180339887 Reorder the terms: -1 + x = 11.180339887 Solving -1 + x = 11.180339887 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 11.180339887 + 1 Combine like terms: -1 + 1 = 0 0 + x = 11.180339887 + 1 x = 11.180339887 + 1 Combine like terms: 11.180339887 + 1 = 12.180339887 x = 12.180339887 Simplifying x = 12.180339887Subproblem 2
x + -1 = -11.180339887 Simplifying x + -1 = -11.180339887 Reorder the terms: -1 + x = -11.180339887 Solving -1 + x = -11.180339887 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -11.180339887 + 1 Combine like terms: -1 + 1 = 0 0 + x = -11.180339887 + 1 x = -11.180339887 + 1 Combine like terms: -11.180339887 + 1 = -10.180339887 x = -10.180339887 Simplifying x = -10.180339887Solution
The solution to the problem is based on the solutions from the subproblems. x = {12.180339887, -10.180339887}
| (T/t-1)+(2/t+1)=(2/t^2-1) | | 3x+45=10x+24 | | (4x+37)=(3x+43) | | 25=X+7 | | 17=7+27t-16t^2 | | 2x^2-x=2-4x | | b=4a-17-26 | | 5y-7+y+57=5y+50-2y | | -6(5p+3)-44=2(2p+3) | | q=2p+8 | | -2(3x-3)+9x-4= | | -3x-5/4 | | 11(c-3)+8=7+c-32 | | 4y-6=2y+2 | | 12000(1+.082)(8)=a | | -30+4k=k-2k | | 865=36000r(10/12) | | 2x^2-10000000x-5=0 | | 2x^2-10000x-5=0 | | 2x^2-1000x-5=0 | | x^2-226x-30=0 | | 1/6(10x-9)=3 | | 3x^3+12x+8=0 | | 114=1800t(8/12) | | 114=1890t(8/12) | | 10y+32x=16.4 | | 2x^2-100x-5=0 | | 35000000*1.88888889= | | 320=5100t | | X-20=-114+6 | | 6y-10y-12y= | | X-20/-114+6 |